The effect of slaughter age on chemical and physical characteristics of dry cured ham of Alentejano pig fattened on acorns - Neves J.; Sabio E.; Monte Costa A.; Freitas A.B.; Tirapicos Nunes J. (Tradition and innovation in Mediterranean pig production, 2000)
Two groups of four hams, eighteen months seasoned, coming from pigs aged 12 or 15 months at slaughter and 130 kg LW (liveweight) were studied. Samples from the outer subcutaneous fat and from the muscle semimembranosus (SM) and biceps femoris (BF) were analysed. The outer subcutaneous fat of older pigs registered a higher amount of C18:1 (57.06 vs 55.34; P either less than or equal to 0.05) and the colour revealed a higher saturation value (0.11 vs 0.09; P either less than or equal to 0.05). Significant differences were not observed for gross chemical composition, fatty acid composition of neutral lipids, neither for pH, aW, NaCl, BVN e NPN values, in both muscles. Though and colour revealed similar values, in both muscles, except for b plus minus and hue that were lower in BF of the older pigs. The aromatic profile did not show significant differences, but a trend for the hams of the younger pigs to present a higher level of linear and branched aldehydes in both muscles was observed. The same situation was observed for ketones, but only in SM.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)